2019
DOI: 10.21873/anticanres.13632
|View full text |Cite
|
Sign up to set email alerts
|

Sinusoidal Obstruction Syndrome and Postoperative Complications Resulting from Preoperative Chemotherapy for Colorectal Cancer Liver Metastasis

Abstract: Background/Aim: The aim of this study was to investigate the effects of preoperative chemotherapy on the healthy, metastasis-free part of the liver in colorectal cancer patients with liver metastasis, and the relationship between chemotherapy and postoperative complications. Patients and Methods: Our study included 90 cases of colorectal cancer liver metastasis resected after preoperative chemotherapy. The patients were divided into three groups according to the received chemotherapy regimen: 20 cases received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…The concomitant use of Cet or Pan might not have side effects. 15 The EGV and non-EGV groups showed no apparent difference in the mean number of cycles (11 vs 12 cycles, respectively). As a result of disease progression, other chemotherapy following FOLFOX was continued in 51 patients (51%) without EGV and 5 patients (83%) with EGV.…”
Section: Comparison Of Baseline Characteristics Betweenmentioning
confidence: 82%
“…The concomitant use of Cet or Pan might not have side effects. 15 The EGV and non-EGV groups showed no apparent difference in the mean number of cycles (11 vs 12 cycles, respectively). As a result of disease progression, other chemotherapy following FOLFOX was continued in 51 patients (51%) without EGV and 5 patients (83%) with EGV.…”
Section: Comparison Of Baseline Characteristics Betweenmentioning
confidence: 82%
“…OXA-induced hepatic sinusoidal obstruction syndrome (HSOS) has been demonstrated in up to 77% of colorectal cancer patients with liver metastasis following OXA-based chemotherapy ( 33 ). Studies have reported that preoperative OXA was associated with HSOS and that this increased postoperative morbidity after partial hepatectomy with colorectal cancer liver metastasisn ( 34 , 35 ). OXA-induced HSOS frequently presents with ascites, jaundice, right upper quadrant pain, splenomegaly with subsequent thrombocytopenia, and portal hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…39 The rationale of precluding the induction treatment has often been a fear of causing parenchymal toxic effects, which could have perioperative and postoperative implications. [40][41][42][43] Previous reports have emphasized the need for randomized prospective trials to determine the best order of treatment for stage IV colorectal cancer with colorectal liver metastases. In contrast, the clinical and biological heterogeneity of this disease indicates that there is no one best treatment for all.…”
Section: Discussionmentioning
confidence: 99%
“…39 The rationale of precluding the induction treatment has often been a fear of causing parenchymal toxic effects, which could have perioperative and postoperative implications. 4043…”
Section: Discussionmentioning
confidence: 99%